EFfectiveness of an intervention to teach physicians how to assist patients to quit smoking in Argentina - Mejia, Raul Mariano (2016)
Introduction: We evaluated an intervention to teach physicians how to help their smoking patients quit compared to usual care in Argentina. Methods: Physicians were recruited from six clinical systems and randomized to intervention (didactic curriculum in two 3-hour sessions) or usual care. Smoking patients who saw participating physicians within 30 days of the intervention (index clinical visit) were randomly sampled and interviewed by telephone with follow-up surveys at months 6 and 12 after the index clinical visit. Outcomes were tobacco abstinence (main), quit attempt in the past month, use of medications to quit smoking, and cigarettes per day. Repeated measures on the same participants were accommodated via generalized linear mixed models. Results: Two hundred fifty-four physicians were randomized; average age 44.5 years, 53% women and 12% smoked. Of 1378 smoking patients surveyed, 81% were women and 45% had more than 12 years of education. At 1 month, most patients (77%) reported daily smoking, 20% smoked some days and 3% had quit. Mean cigarettes smoked per day was 12.9 (SD = 8.8) and 49% were ready to quit within the year. Intention-to-treat analyses did not show significant group differences in quit rates at 12 months when assuming outcome response was missing at random (23% vs. 24.1%, P = .435). Using missing=smoking imputation rule, quit rates were not different at 12 months (15.6% vs. 16.4% P = .729). Motivated smokers were more likely to quit at 6 months (17.7% vs. 9.6%, P = .03). Conclusions: Training in tobacco cessation for physicians did not improve abstinence among their unselected smoking patients.